Nutritional Status of Female Adolescents and Early Adults in Aseer Region, Abha District - Sachithananthan, Vedavalli; Jehan, Nusreth (Journal of Nutritional Therapeutics, 2015)
The nutritional status of adolescents and early adults is ‘at risk’ because of the booming up of the fast food industry and decline in physical activity. An attempt was made in this study to understand the nutritional status of female adolescents and early adults in Aseer region of Abha district. Using a structured and validated questionnaire, the age, height, weight, waist circumference, hip circumference income and education of parents and physical activity were assessed. The anthropometric profile (Mean) indicates that almost all parameters were within normal range. However 36.6 percent of the subjects fell in the ‘at risk’ category of waist hip ratio. With respect to the body mass index, a majority of the subjects were normal weight (68.3%), followed by 16.8 percent who were overweight and 14.9 percent underweight. In conclusion it can be stated that the overweight and underweight subjects should be brought to the normal weight category by consuming a nutritionally balanced diet and adequate physical activity to prevent malnutrition problems and chronic diseases for the underweight and overweight adolescents and early adults in the long run.